Prespektif Hukum Terhadap Pemutusan Hubungan Kerja Dan Kompensasi Pesangon: Analisis Studi Kasus pada PT. JSU - Fatimah Cahya Amani; Nirwasita Zada Paramesti; Jasmine Fatiha Jamaila; Dwi Desi Yayi Tarina (IAI Nasional Laa Roiba Bogor, 2024)
Termination of employment and severance compensation are important issues in the scope of industrial relations between workers and employers. A legal perspective can provide a framework for resolving the above cases. This study aims to understand the benefits of a legal perspective on termination of employment and severance compensation in PT cases. Primary Self-Help Services. This research uses a literature study carried out through reviewing documents, statutory regulations and related literature. The findings of this study show that a legal perspective that considers workers' rights and legal provisions related to termination of employment can provide many benefits for both parties and prevent conflicts between them. Employers must comply with the rules regarding the payment of severance pay to workers when termination of employment (PHK) occurs so that workers can obtain their rights in a timely manner and in the appropriate amount. A legal perspective can also minimize the risk of future disputes regarding severance compensation so that good industrial relations can be formed between the two parties. Keywords: Layoffs, Severance Compensation, Legal Perspective.